Social dialogue and occupational diseases in Europe : ten lines of action to strengthen and harmonize the prevention and compensation policies (Bruxelles, 2006)
"This brochure is the fruit of a close cooperation between two trade federations from the chemistry sector - CSC Énergie-chimie (B) and FEMCACISL (IT) -, and INAS (IT), that provides legal guidance to workers who are the victims of occupational diseases and organises the individual protection of workers in the field of social security. Its aim is to present a synthesis of the reflections and comments that were expressed by those three organisations at a seminar held in Padua (Italy) from March 29th until April 1st 2006, that was attended by many European trade union organisations, the European trade union federation of chemistry (EMCEF), a representative of the EC, as well as representatives of insurance institutions from the Member states and physicians."